Vygotsky's psychology : a biography of ideas - Kozulin, Alex (Harvard Univesity Press, 1990)
Lev Vygotsky (1896-1934), whose work was until recently known only to a small circle of Western psychologists, is now viewed as 'the Mozart of psychology' and one of the major theorists of twentieth-century social science. Alex Kozulin, translator of his work and distinguished Russian-American psychologist, has written a major intellectual biography about Vygotsky's life; his psychological theory of language, thought and development; and the posthumous life of his ideas. Kozulin's biography of Vygotsky reflects many of the conflicts of twentieth-century psychology--from the early battles between introspectionists and reflexologists to the current argument concerning the cultural and social, rather than natural, construction of the human mind. Vygotsky was a contemporary of Freud and Piaget, and his tragically early death and the Stalinist suppression of his work ensured that his ideas did not have an immediate effect on Western psychology. But the last two decades have seen his psychology become highly influential while that of other theoretical giants has faded. "Vygotsky's Psychology: A Biography of Ideas" is the first comprehensive account of Vygotsky's theories and their relationship to Russian and Western intellectual culture in the twentieth century.